Antibiotic Susceptibility Patterns in Patients with Chronic Kidney Disease in Bangladesh: A Comprehensive Analysis of Clinical Isolates - Latif, Abdul; Kar, Shubharthi; Das, Shantanu; Islam, Md Saiful (Jalalabad Medical Journal, 2025)
Chronic kidney disease (CKD) is a significant health concern in Bangladesh, with patients frequently experiencing infectious complications due to immunocompromised status. The study aimed to investigate the antibiotic susceptibility patterns among patients with chronic kidney disease (CKD) in Bangladesh. This cross-sectional study was conducted at Jalalabad Ragib-Rabeya Medical College in Sylhet, Bangladesh, from June 2022 to May 2023. Through a comprehensive analysis of clinical isolates from 205 CKD patients, the study reveals varying susceptibility profiles across multiple antibiotics. Among the antibiotics tested, carbapenems, specifically, meropenem and imipenem, exhibit high sensitivity rates exceeding 88% against diverse microbial isolates. This highlights their efficacy as broad-spectrum agents. Amikacin, on the other hand, emerges as a reliable treatment option, showing substantial sensitivity ranging from 50% to 100% against most isolates. Other antibiotics, such as ciprofloxacin and levofloxacin, demonstrate moderate to high sensitivity. They are particularly effective against prevalent pathogens like Escherichia coli and Pseudomonas. However, some antibiotics, including ceftazidime and cefuroxime, show limited efficacy against specific isolates. These findings underscore the importance of judicious antibiotic selection and surveillance in CKD patients. Such measures are crucial for optimising treatment outcomes and minimising antibiotic resistance. The study also highlights the need for ongoing antibiotic stewardship efforts. It emphasises the significance of tailored therapy based on local susceptibility patterns to effectively combat infectious complications in CKD patients. Jalalabad Med J 2024; 21 (2); 47-56